Two negative minima of the first normal stress difference in a cellulose-based cholesteric liquid crystal: Helix uncoiling - Echeverria Zabala, Coro (2017)
The shear rate dependence of material functions such as shear viscosity (η) and the first normal stress difference (N1) were given and interpreted earlier by Kiss and Porter. Their widely accepted work revealed the possibility of having a negative minimum of N1 for polymeric liquid crystals. In this work, we disclose for the first time the evidence of two negative N1 minima on a sheared cellulosic lyotropic system. The lower shear rate minimum is ascribed to the uncoiling of the cholesteric helix, as theoretically predicted earlier. Our findings contribute also to the understanding of the other minimum already reported in the literature and attributed to the nematic director tumbling mode. Moreover, the elastic change that the LC-HPC sample undergoes during the helix unwinding of the cholesteric structure is also by means of oscillatory measurements. This study is a contribution for the understanding of the structure-properties relationship linked with the complex rheological behavior of chiral nematic cellulose-based systems and may help to improve their further processing. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.